Mycoplasma contamination-mediated attenuation of plasmid DNA transfection efficiency is augmented via L-arginine deprivation in HEK-293 cells - Yin, Zi-fei (Zhejiang University Press, 2019)

(untitled) (J Zhejiang Univ Sci B)
Mycoplasma infection is the most prevalent contamination in cell culture. Analysis of cell culture in laboratories from different countries shows that mycoplasma contamination ranges from 15% to 80% and, in some cases, even reaches 100% (Chernov et al., 2014). Whilst mycoplasma infection is not visible to the naked eye in cell culture, the consequences of mycoplasma contamination have been shown to induce a number of cellular changes, for example, increased resistance to chemotherapeutic drugs. Therefore, any results obtained from tissue culture studies, in the presence of mycoplasma contamination, potentially render the data invalid (Kim et al., 2015; Gedye et al., 2016). As such, mycoplasmas are not harmless bystanders and cannot be ignored in in vitro studies.